2001
DOI: 10.1177/00220345010800100501
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Regulation of MMP-20 in Human Tongue Carcinoma Cells

Abstract: Human matrix metalloproteinase-20 (MMP-20, enamelysin) fragments the enamel-specific protein amelogenin and has been shown to be synthesized exclusively by odontoblasts and ameloblasts and in certain odontogenic tumors. Here we demonstrate, for the first time, the expression of MMP-20 mRNA and protein in two carcinoma cell lines originating from the tongue. Treatment of the SCC-25 and HSC-3 cells with phorbol 12-myristate 13-acetate (10 nmol/L) up-regulated MMP-20 mRNA and protein expression by up to 1.6-fold,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 27 publications
3
27
0
1
Order By: Relevance
“…In support of this mechanism, radiotherapy increases the expression and activation of matrix metalloproteinases (MMPs) in various tissues (Araya et al, 2001;Strup-Perrot et al, 2006). To this end, we have shown that MMP-20, a type IV collagenase (Väänänen et al, 2001), is localized to the DEJ and that its processing is altered in teeth post-radiotherapy (McGuire et al, 2014a).…”
Section: Discussionmentioning
confidence: 82%
“…In support of this mechanism, radiotherapy increases the expression and activation of matrix metalloproteinases (MMPs) in various tissues (Araya et al, 2001;Strup-Perrot et al, 2006). To this end, we have shown that MMP-20, a type IV collagenase (Väänänen et al, 2001), is localized to the DEJ and that its processing is altered in teeth post-radiotherapy (McGuire et al, 2014a).…”
Section: Discussionmentioning
confidence: 82%
“…The following polyclonal antibodies were used in the immunohistochemical stainings: laminin-5 g2-chain (1 : 1000) (Pyke et al, 1995), (Hanemaaijer et al, 1997), MMP-9 (1 : 1000, Neomarkers, Fremont, CA, USA), MMP-20 (1 : 1000) (Väänänen et al, 2001), MMP-28 (1 : 500) (Lohi et al, 2001) and factor VIII (1 : 800, Dako A/S, Glostrup, Denmark). MMP-2 (1 : 2000, Suomen Bioanalytiikka, SBA, Turku, Finland), MMP-7 (1 : 80, Calbiochem, La Jolla, CA, USA), integrin avb6 (6.2G2 at 0.5 mg ml À1 (Weinreb et al, 2004), Biogen Idel, Inc., Cambridge, MA, USA), COX-2 (1 mg ml À1 , Cayman Chemical, Ann Arbor, Michigan, USA) and CD31 (1 : 30, DakoCytomation, Glostrup, Denmark) antibodies were monoclonal.…”
Section: Antibodiesmentioning
confidence: 99%
“…It was demonstrated that MMP-20 was found to be expressed in oral squamous cell carcinoma (SCC) cells in vitro 196 but to date they are the only cells outside the tooth forming cells that have been shown to express MMP-20. In MMP-20 knock-out mice, an amelogenesis imperfecta phenotype was seen, but the circumpulpal dentine seemed apparently unaffected 23 .…”
Section: Growth Factorsmentioning
confidence: 99%